Reasons- why ACI Limited should start B2B online store for consumer brand - Anam, S. M. Shad-E- (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.